The Effect Of Financial Literacy And Income On Credit Taking Decisions With Financial Behavior As A Moderating Variable In Pontianak City MSMES - Virani Mbere; Heni Safitri (UNIVED Press, 2024)
This study aims to examine how financial behavior affects the relationship between financial literacy, income, and lending decisions. This research was conducted on MSMEs in Pontianak City that were officially registered with the Pontianak City Office of Cooperatives, Micro, and Small Enterprises in 2023. The research method used was quantitative with descriptive analysis. To select the research sample, a purposive selection strategy was used with a total sample size of 150 MSMEs. Moderated Regression Analysis was used to test the moderating effect of financial behavior on the correlation between financial literacy, income, and loan decisions. The findings show that financial literacy has a favorable and large impact on credit decisions, while income has an adverse and large impact. In addition, financial literacy and income play an important role in determining lending decisions. The findings of the moderation test using MRA show that financial behavior can moderate the relationship between financial literacy and income on lending decisions.